Grinding fluid applied to ceramic tiles as well as use method and application of grinding fluid

By using an abrasive slurry containing specific raw materials for indirect polishing on ceramic tiles, the problems of scratch marks and poor wear resistance caused by traditional polishing technology on thin glazed ceramic tiles are solved, achieving better pollution resistance and wear resistance. .

CN119351055APending Publication Date: 2025-01-24QINGYUAN GANI CERAMICS CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510492.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional polishing technology has problems of scratch marks and poor wear resistance on thin-glazed ceramic tiles, especially when the glaze layer thickness is less than 0.5mm.

Method used

An abrasive liquid containing inorganic abrasive particles, plastic particles, polyhydroxyl hyperbranched resin, divalent acid ester DBE and solid dispersant is used to reduce the scratch marks on the brick surface through indirect polishing.

Benefits of technology

It significantly reduces scratch marks and "hornet's nest" phenomenon on the surface of ceramic tiles, improves the pollution resistance and wear resistance of ceramic tiles, and improves production yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351055A_ABST
    Figure CN119351055A_ABST
Patent Text Reader

Abstract

The invention discloses a grinding fluid applied to ceramic tiles as well as a use method and application thereof, and relates to the field of ceramic polishing, the grinding fluid comprises the following raw materials in percentage by mass: 12-20% of inorganic abrasive particles, 5-10% of plastic particles, 10-15% of polyhydroxy hyperbranched resin, 25-50% of dibasic acid ester DBE and 20-31% of a solid dispersant. The inorganic abrasive particles are composed of main stone powder with the Mohs hardness range of 2.7-4 and auxiliary stone powder with the Mohs hardness range of 5-8, the weight ratio of the main stone powder to the auxiliary stone powder is (7-18): 1, the particle size range of the solid particles is 250-500 microns, and the hydroxyl value range of the polyhydroxy hyperbranched resin is 480-700 mgKOH / g. The grinding fluid is applied to a polishing process and applied to the surface of a ceramic tile, so that indirect polishing is formed between a polishing grinding block and the ceramic tile, and scratches on the surface of the ceramic tile are at least remarkably reduced through the special raw material ratio of the grinding fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic polishing, and in particular to a grinding liquid applied to ceramic tiles, a use method and application thereof, and a tile polishing machine. Background Art

[0002] The glaze thickness of traditional fully polished glazed tiles is 0.5-1.5mm. The thicker the glaze layer, the less conducive it is to highlight the texture pattern. The thin-polished glaze with a glaze layer thickness of less than 0.5mm has an advantage in highlighting the texture pattern, so a new trend of using thin-polished glaze has been formed. The traditional polishing method is to directly contact and polish the glaze surface of the tile through the grinding block combination on the polishing machine at a certain speed and pressure. However, the traditional polishing technology has many technical defects when applied to thin-polished glaze. First, the thin-polished glaze is easily worn through by the polishing grinding block, forming a "hornet's nest", which affects the tile surface effect and pollution resistance, and has poor wear resistance; secondly, if the pressure control of the polishing machine head is slightly deviated and the pressure is too deep, the shading pattern is easily scratched to form "hair" marks, which seriously reduces the production yield of tiles. Based on this, a polishing solution suitable for thin-polished glazed tiles is urgently needed. Summary of the invention

[0003] The main purpose of the present invention is to propose a grinding liquid for ceramic tiles. The grinding liquid is used in the polishing process and applied to the surface of the ceramic tile so that the polishing block and the ceramic tile form indirect polishing. The scratch marks are significantly reduced through the raw material ratio of the grinding liquid. It can be suitable for the indirect polishing of thin glazed ceramic tiles with a glaze layer thickness of less than 0.5 mm, significantly reducing scratch marks and avoiding the formation of "hornet's nest" on the surface of the ceramic tile. One or more other technical problems in the background technology are solved through further technical solutions. The secondary purpose of the present invention is to propose the use method and application of the aforementioned grinding liquid.

[0004] To achieve the above-mentioned purpose, the present invention proposes a grinding liquid for ceramic tiles, wherein the raw material composition comprises, by mass percentage, 12-20% inorganic abrasive particles, 5-10% plastic particles, 10-15% polyhydroxy hyperbranched resin, 25-50% dibasic acid ester DBE and 20-31% solid dispersant.

[0005] The inorganic abrasive grains are composed of main stone powder with a Mohs hardness range of 2.7 to 4 and auxiliary stone powder with a Mohs hardness range of 5 to 8, the main stone powder and the auxiliary stone powder are in a weight ratio of 11 to 18:1, the particle size range of the inorganic abrasive grains and the plastic particles is 250 to 500 μm, and the hydroxyl value range of the polyhydroxy hyperbranched resin is 480 to 700 mgKOH / g.

[0006] The invention adds polyhydroxy hyperbranched resin to the raw material of the grinding liquid, and the hydroxyl groups in the hyperbranched resin are wrapped and attached to the surface of the polishing abrasive block of the inorganic material, thereby significantly reducing the scratches on the brick surface caused by the polishing abrasive block in an arc swinging state in the working state (specifically, in the traditional polishing method, a certain inclination angle is formed when the abrasive block swings, so that the local corner directly contacts the brick surface to cause scratches). The inorganic abrasive composed of main stone powder and auxiliary stone powder with a specific hardness and weight ratio within a certain particle size range plays a role in removing the tip, and the plastic particles have no cutting effect. The cutting amount is reduced to a certain extent in the formula to protect the brick surface. The inorganic abrasive and the plastic particles are combined in a specific ratio, which can remove the tip of the tile surface and buffer and protect the brick surface at the same time. At the same time, the divalent acid ester DBE is used as a solvent, which is not easy to evaporate due to absorbing the heat generated by friction, and can avoid the resin and the brick being adhered to the brick and difficult to clean, resulting in subsequent wax marks and wax residues on the brick surface. The solid dispersant is dissolved in the solvent, so that the solid particles composed of the inorganic abrasive and the plastic particles are dispersed without sedimentation. The grinding liquid of the present invention is applied to the polishing process and applied to the surface of the tile so that the polishing abrasive block and the tile form indirect polishing. Through the special raw material ratio of the grinding liquid, the generation of scratch marks on the tile surface can at least be significantly reduced.

[0007] The multi-hydroxy hyperbranched resin with a hydroxyl value ranging from 480 to 700 mgKOH / g forms a good wrapping and adhesion on the surface of the polishing abrasive block of the inorganic material. The hydroxyl-containing hyperbranched resin is preferably at least one of the HyPer E102, HyPerH10, HyPer H20, HyPer H30, and HyPerH40 series products of Wuhan Hyperbranched Resin Co., Ltd.

[0008] Specifically, the solid dispersant is preferably at least one of the Gaotai 790, Gaotai P90 and Gaotai P30 models of products among Guangzhou Qilang Chemical Products.

[0009] Preferably, according to the mass percentage of the grinding liquid raw materials, the main stone powder is composed of 10-15% fluorite powder and 1-3% calcite powder, and the auxiliary stone powder is 1-2% quartz sand. The inorganic abrasive particles in the above proportions can achieve a better de-tip effect on the brick surface and obtain a softer polishing effect.

[0010] Preferably, according to the mass percentage of the grinding liquid raw materials, 0.01-5% of a co-solvent is also included, and the co-solvent includes at least one of butanol, ethyl acetate, acetone and D40. The co-solvent helps dissolve the polyhydroxy hyperbranched resin.

[0011] Preferably, the main stone powder includes at least one of fluorite powder and calcite powder.

[0012] Preferably, the auxiliary stone powder comprises at least one of quartz sand and feldspar powder.

[0013] Preferably, the plastic particles include at least one of polymethyl methacrylate (PMMA for short), polypropylene (PP for short), acrylonitrile-butadiene-styrene copolymer (ABS for short), polyoxymethylene (POM for short) and polycarbonate (PC for short).

[0014] Preferably, the plastic particles are polymethyl methacrylate, the main stone powder is composed of fluorite powder and calcite powder, and the auxiliary stone powder is quartz sand;

[0015] The grinding liquid comprises, by weight percentage, 10% of fluorite powder, 3% of calcite powder, 2% of quartz sand, 5% of polymethyl methacrylate, 10% of polyhydroxy hyperbranched resin, 20% of solid dispersant, 5% of butanol and 45% of dibasic acid ester DBE.

[0016] Combined with the optimal polishing liquid raw material composition, the surface pollution resistance, wear resistance and production yield of the tiles after indirect polishing are optimal. The surface of the tiles has a soft luster and there are no "hornet's nests" or scratches on the surface of the tiles.

[0017] The present invention provides a method for using the above-mentioned grinding liquid, which is configured according to the raw material formula, stirred evenly to obtain the grinding liquid, and the grinding liquid is evenly applied to the surface of the ceramic tile, and the surface of the ceramic tile is polished using a polishing device, and the polishing block on the polishing device has a height difference of 0.2 to 0.5 mm with the brick surface of the ceramic tile in the working state. In the working state, the height difference between the polishing block and the brick surface is equal to or slightly lower than the particle size of the ground solid particles, and the polishing block forms indirect polishing with the brick surface through the grinding liquid. In the working state, the thin polishing glaze layer is not easily polished through by the polishing module to form a hornet's nest, which affects the brick surface effect and pollution resistance, and is also conducive to avoiding the scratching of the shading pattern to form "hair" marks due to slight deviations in the pressure control of the polishing machine head.

[0018] Preferably, the grinding liquid is applied to the surface of the ceramic tile by spray coating, so that the grinding liquid fully covers the tile surface.

[0019] The present invention provides the above-mentioned grinding liquid, which is applied to the polishing process of ceramic tiles with a glaze layer thickness of ≤0.5 mm. Preferably, the glaze layer thickness of the ceramic tiles is 0.2-0.3 mm.

[0020] Ceramic tiles with a thickness of less than 0.5mm are thin-glazed tiles. The above-mentioned grinding liquid is applied to the thin-glazed tiles by indirect polishing. Compared with the traditional polishing technology that uses polishing blocks to directly contact and grind the tile surface, it can significantly reduce the "hornet's nest" and scratches on the tile surface and improve the tile production yield. The above effects can be achieved on ceramic tiles with a glaze layer thickness of only 0.2 to 0.3mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0022] Figure 1 This is a real picture of the scratches on the surface of a ceramic tile after direct polishing under a microscope at 20 times magnification;

[0023] Figure 2 This is a real picture of a ceramic tile with no scratches or "hornet's nest" after indirect polishing with abrasive liquid under a microscope at 20 times magnification;

[0024] Figure 3 This is a real picture of the "hornet's nest" brick surface produced by direct polishing of ceramic tiles;

[0025] Figure 4 This is a real picture of the "hornet's nest" on the surface of ceramic tiles produced after direct polishing and the contaminated brick surface after anti-fouling testing.

[0026] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0028] The present application proposes a grinding liquid for ceramic tiles, wherein the raw materials include, by mass percentage, 12-20% inorganic abrasive particles, 5-10% plastic particles, 10-15% polyhydroxy hyperbranched resin, 25-50% dibasic acid ester DBE and 20-31% solid dispersant.

[0029] The inorganic abrasive grains are composed of main stone powder with a Mohs hardness ranging from 2.7 to 4 and auxiliary stone powder with a Mohs hardness ranging from 5 to 8, the weight ratio of the main stone powder to the auxiliary stone powder is 11 to 18:1, the particle size range of the inorganic abrasive grains and plastic particles is 250 to 500 μm, and the hydroxyl value range of the polyhydroxy hyperbranched resin is 480 to 700 mgKOH / g.

[0030] In a preferred embodiment, according to the mass percentage of the grinding liquid raw materials, the main stone powder is composed of 10-15% fluorite powder and 1-3% calcite powder, and the auxiliary stone powder is 1-2% quartz sand.

[0031] In a preferred embodiment, according to the mass percentage of the grinding liquid raw material, 0.01-5% of a co-solvent is further included, and the co-solvent includes at least one of butanol, ethyl acetate, acetone and D40;

[0032] In a preferred embodiment, the main stone powder includes at least one of fluorite powder and calcite powder; the auxiliary stone powder includes at least one of quartz sand and feldspar powder; and the plastic particles include at least one of polymethyl methacrylate, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyoxymethylene and polycarbonate.

[0033] The present application also provides a method for using a grinding liquid, which is configured according to a raw material formula, stirred evenly to obtain a grinding liquid, and the grinding liquid is evenly applied to the surface of a ceramic tile. The surface of the ceramic tile is polished using a polishing device, and the polishing block on the polishing device has a height difference of 0.2 to 0.5 mm with the tile surface of the ceramic tile in a working state.

[0034] In a preferred embodiment, the grinding liquid is applied to the surface of the ceramic tile by flow coating.

[0035] The technical scheme of the present invention is further described in detail below in conjunction with specific embodiments or comparative examples. In the following embodiments and comparative examples, raw materials, reagents, etc. not otherwise specified are all commercially available, and the same batch of raw materials or reagents are used in the embodiments and comparative examples; the preparation methods without special conditions are all prepared by conventional, well-known preparation methods.

[0036] A ceramic tile with a thin glaze layer having a glaze layer thickness of 0.2 to 0.3 mm is provided for performance testing after direct polishing or indirect polishing with a grinding fluid in the following specific embodiments or specific comparative examples.

[0037] In the above-mentioned direct polishing or indirect polishing polishing process, the following polishing process parameters are adopted for example only: pressure 0.1-0.3Mpa, polishing abrasive blocks consist of 10 groups of 400-mesh low-light modules, 10 groups of 800-mesh low-light modules and 10 groups of 240-mesh low-light modules.

[0038] The method for using the grinding liquid is as follows: the grinding liquid is prepared according to the raw material formula composition of the specific embodiment or the specific comparative example, and the grinding liquid is evenly stirred to obtain the grinding liquid, and the grinding liquid is evenly applied to the surface of the ceramic tile. The polishing abrasive block has a height difference of 0.2 to 0.5 mm with the tile surface in the working state, and the particle size range of the solid particles in the grinding liquid is 250 to 500 μm.

[0039] In the following specific embodiments or comparative examples, unless otherwise specified, the plastic particles are all made of polymethyl methacrylate, the polyhydroxy hyperbranched resin is all made of HyPer H204 (the main component is heat-resistant terminal hydroxyl hyperbranched polyester with a hydroxyl value of 490 mgKOH / g), the solid dispersant is all made of BASF 4040 (the main component is polyacrylate ammonium salt), and the cosolvent is all made of n-butanol.

[0040] Among them, the stone powder raw materials and hardness involved in inorganic abrasives are: fluorite powder, Mohs hardness is 4; calcite powder, Mohs hardness is 3; quartz sand, Mohs hardness is 7; feldspar powder, Mohs hardness is 6-6.5.

[0041] In the specific implementation of the present invention, the various performance indicators of the ceramic tile after direct polishing or indirect polishing with abrasive liquid are measured by the following methods or standards:

[0042] 1. Wear resistance level

[0043] Carry out the corresponding glazed tile surface wear resistance test in the national standard T4100-2015 for ceramic tiles;

[0044] 2. Antifouling test

[0045] Use oil-based pen to paint, and scrub with hand washing powder after the ink dries. Repeat three times. If there is no pollution when observing from 1m away, it is qualified.

[0046] 3. No scratch yield

[0047] Small test of 100 pieces, random inspection of 20 pieces.

[0048] Calculate the scratch-free yield rate = number of scratch-free bricks / 20*100%;

[0049] 4. Use a gloss meter to test the gloss;

[0050] 5. Observe the appearance of the brick surface.

[0051] Example 1

[0052] The raw material composition of the grinding liquid is configured according to the mass percentage in the following table.

[0053]

[0054] The composition of inorganic abrasive raw materials is shown in the following table.

[0055] Serial number Example 1 Main stone powder Fluorite powder 7.5%, calcite powder 7.5% Auxiliary stone powder Quartz sand 1% Weight ratio of main stone powder to auxiliary stone powder 15:1

[0056] Comparative Example 1

[0057] The raw material composition of the grinding liquid is configured with reference to Example 1, except that the raw material composition of the inorganic abrasive is different.

[0058]

[0059] Comparative Example 2

[0060] The inorganic abrasive composition in the grinding liquid is configured with reference to Example 1, except that the mass percentages of inorganic abrasive particles and plastic particles in the raw materials of the grinding liquid are different.

[0061]

[0062] The ceramic tiles were subjected to performance testing after indirect polishing with abrasive fluid. The data of the above specific embodiment are as follows:

[0063]

[0064] From the above data, we can conclude that:

[0065] By comparing Example 1 with Comparative Examples 1-1 to 1-2, it can be seen that when the Mohs hardness of the main stone powder in the inorganic abrasive is in the range of 2.7 to 4, the Mohs hardness of the auxiliary stone powder is in the range of 5 to 8, and the weight ratio of the main stone powder: the auxiliary stone powder is in the range of 7 to 18:1, the scratch marks are limited and reduced, and the pollution resistance, wear resistance and scratch-free yield are improved. When the Mohs hardness of the main stone powder is too high, such as in Comparative Example 1-1, the brick surface is too ground; when the Mohs hardness of the auxiliary stone powder is too low, such as in Comparative Example 1-2, the brick surface is insufficiently ground, indicating that the hardness and weight ratio of the main stone powder and the auxiliary stone powder affect the indirect polishing effect, and the main stone powder and the auxiliary stone powder need to be matched with a certain hardness and weight ratio to achieve a good indirect polishing effect.

[0066] By comparing Example 1 with Comparative Examples 2-1 and 2-2, it can be seen that in the mass percentage of the grinding liquid raw materials, when the inorganic abrasive is 12-20% and the plastic particles are 5-10%, a good indirect polishing effect is achieved. When no plastic particles are added, such as in Comparative Example 2-1, obvious scratches are produced on the brick surface, and the scratch-free yield, wear resistance grade and pollution resistance performance are significantly reduced, and the gloss is too high, reaching more than 40°; when the proportion of plastic particles is too high, such as in Comparative Example 2-2, the brick surface is not polished enough, the gloss is too low, below 10°, and the pollution resistance is significantly reduced.

[0067] Example 2

[0068] The raw material composition of the grinding liquid is configured according to the mass percentage in the following table, wherein butanol is used as the co-solvent.

[0069]

[0070] The main stone powder of the inorganic abrasive is composed of 10% fluorite powder and 3% calcite powder, and the auxiliary stone powder is 2% quartz sand.

[0071] The ceramic tiles were subjected to performance testing after indirect polishing with abrasive fluid. The data of the above specific embodiment are as follows:

[0072] Serial number Wear resistance grade Pollution resistance Scratch-free yield Glossiness Appearance after washing Example 1 Level 3 1500 rpm qualified 100% 25-30° No hornet's nest Example 2 Level 3 2100 rpm qualified 100% 28-30° No hornet's nest

[0073] From the above data, we can conclude that:

[0074] By comparing Example 1 with Example 2, it can be seen that according to the mass percentage of the grinding liquid raw materials, when the main stone powder is composed of 10-15% fluorite powder and 1-3% calcite powder, and the auxiliary stone powder is 1-2% quartz sand, the gloss range of the tile surface is further narrowed, the light feeling is more uniform, and the wear resistance level is further improved. Example 2 is the most preferred embodiment.

[0075] Comparative Example 3

[0076] The raw material composition in the grinding liquid, the main stone powder and auxiliary stone powder raw materials of the inorganic abrasive, and the weight ratio are configured with reference to Example 1, except that: the raw material composition of the grinding liquid is changed.

[0077] In Comparative Example 3-1, there is no polyhydroxy hyperbranched resin, and other raw material components are adaptively changed;

[0078] In Comparative Example 3-2, the dibasic acid ester DBE solvent was replaced with D40.

[0079] The ceramic tiles were subjected to performance testing after indirect polishing with abrasive fluid. The data of the above specific comparative ratios are as follows:

[0080]

[0081]

[0082] From the above data, we can conclude that:

[0083] By comparing Example 1 with Comparative Example 3-1, it can be seen that when polyhydroxy hyperbranched resin is not added to the grinding liquid component, it is difficult to avoid scratches on the brick surface and the polishing abrasive block during the indirect polishing process, and the scratch-free yield rate is significantly reduced; by comparing Example 1 with Comparative Example 3-2, it can be seen that when other conventional solvents are used to replace divalent ester DBE in the grinding liquid component, wax marks and wax residues are subsequently produced on the brick surface.

[0084] Comparative Example 4

[0085] Comparative Example 4-1 was directly polished according to the polishing process in the specific embodiment.

[0086] Comparative Example 4-2 uses diamond brush soft polishing for direct polishing.

[0087] The ceramic tiles were directly polished with abrasive liquid and then tested for performance. The data of the above specific embodiment are shown in the following table:

[0088] Serial number Wear resistance grade Pollution resistance Scratch-free yield Glossiness Appearance after washing Example 1 Level 3 1500 rpm qualified 100% 25-30° No hornet's nest Comparative Example 4-1 Level 3 600 rpm Failure 90% 35-45° More hornet's nests Comparative Example 4-2 Level 3 600 rpm qualified 90% 30-35° No hornet's nest

[0089] It can be seen from the above data that the direct polishing method in Comparative Example 4-1 caused obvious hornet's nests and obvious scratches, and the pollution resistance and wear resistance were extremely poor. The indirect polishing using the grinding liquid of the present application in Example 1 was close to the soft polishing using a diamond brush in Comparative Example 4-2 in terms of pollution resistance, and also did not produce a hornet's nest in appearance. However, Example 1 was significantly better in terms of scratch performance and wear resistance level on the brick surface, and the glossiness was softer.

[0090] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A grinding fluid for ceramic tiles, characterized in that: According to the mass percentage, the raw material composition includes: 12-20% inorganic abrasive, 5-10% plastic particles, 10-15% polyhydroxy hyperbranched resin, 25-50% dibasic acid ester DBE and 20-31% solid dispersant. The inorganic abrasive grains are composed of main stone powder with a Mohs hardness range of 2.7 to 4 and auxiliary stone powder with a Mohs hardness range of 5 to 8, the main stone powder and the auxiliary stone powder are in a weight ratio of 7 to 18:1, the particle size range of the inorganic abrasive grains and the plastic particles is 250 to 500 μm, and the hydroxyl value range of the polyhydroxy hyperbranched resin is 480 to 700 mgKOH / g.

2. The grinding liquid for ceramic tiles according to claim 1, characterized in that: According to the mass percentage of the grinding liquid raw materials, the main stone powder is composed of 10-15% fluorite powder and 1-3% calcite powder, and the auxiliary stone powder is 1-2% quartz sand.

3. The grinding liquid for ceramic tiles according to claim 1, characterized in that: According to the mass percentage of the grinding liquid raw materials, 0.01-5% of a co-solvent is also included, and the co-solvent includes at least one of butanol, ethyl acetate, acetone and D40.

4. The grinding liquid for ceramic tiles according to claim 1, characterized in that: The main stone powder includes at least one of fluorite powder and calcite powder; The auxiliary stone powder comprises at least one of quartz sand and feldspar powder; The plastic particles include at least one of polymethyl methacrylate, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyoxymethylene and polycarbonate.

5. The method for using the polishing liquid according to claim 4, characterized in that: The plastic particles are polymethyl methacrylate, the main stone powder is composed of fluorite powder and calcite powder, and the auxiliary stone powder is quartz sand; The grinding liquid comprises, by weight percentage, 10% fluorite powder, 3% calcite powder, 2% quartz sand, 5% polymethyl methacrylate, 10% polyhydroxy hyperbranched resin, 20% solid dispersant, 5% butanol and 45% dibasic acid ester DBE.

6. The method for using the polishing liquid according to any one of claims 1 to 5, characterized in that: The raw materials are configured according to the formula and stirred evenly to obtain a grinding liquid, the grinding liquid is evenly applied to the surface of the ceramic tile, and the surface of the ceramic tile is polished using a polishing device. The polishing block on the polishing device has a height difference of 0.2 to 0.5 mm with the tile surface of the ceramic tile in a working state.

7. The method for using the polishing liquid according to claim 6, characterized in that: The grinding liquid is applied to the surface of the ceramic tile by flow coating.

8. The grinding liquid for ceramic tiles according to any one of claims 1 to 5, characterized in that: Applicable to the polishing process of ceramic tiles with glaze layer thickness ≤ 0.5mm.

9. The grinding liquid for ceramic tiles according to claim 8, characterized in that: The thickness of the glaze layer of the ceramic tile is 0.2-0.3 mm.